Hybrid manufacturing of aluminium parts combining additive and conventional technologies—mechanical and thermal properties - Silva, Eva C. (2022)
Metal additive-manufacturing technologies enable the production of complex geometries. However, high manufacturing costs hinder these technologies being employed in some industries. In this sense, a hybrid strategy is presented in this paper, to achieve the best of additive and subtractive technologies, offering economic advantages. AlSi10Mg aluminium powder was deposited on AW-6082 pre-machined substrates and mechanical and thermal properties of these specimens were evaluated considering the application of a stress relief heat treatment. The results were especially good in the compressive mechanical properties and in the thermal properties: compressive properties were improved by up to 27%, and the specific heat capacity and coefficient of thermal expansion were reduced by up to 38%, compared to additively manufactured AlSi10Mg. Therefore, hybrid manufacturing can be a profitable solution (i) in thermal management applications, (ii) when compressive loads are presented, or (iii) to repair damaged parts, providing a circular economy, as presented in a case study of this paper.